THE FINANCING DECISION, SIZE AND FIRM VALUE: A CONCEPTUAL REVIEW - Hasnawati, Sri (FEB - Universitas Lampung, 2020)
This study intends to conduct a non-systematic literature review on empirical and theoretical studies of capital structure policies in relation to firm value, as well as reviewing its nature and dimensions. Until now, no consensus has emerged, and the results cannot be concluded. This study also tries to include empirical of capital structure policies and firm value from various countries, which show that the phenomenon of capital structure policies and firm value differs from one country to another. Various discussions on capital structure policies and firm value have resulted in a literature review and its development over time. Another development is the link between capital structure and size. Size can determine the company's capital structure related to access to sources of financing. Generally, large companies are easier to obtain external financing sources than small companies.